Islamic Boarding School-Based Madrasah Curriculum Development Design at Madrasah Aliyah Mizanul Kubro Binjai - Charles Rangkuti; Manshuruddin (Indonesian Journal of Contemporary Multidisciplinary Research, 2023)
This study aims to analyze the design of developing a boarding school-based madrasah curriculum at MAS Mizanul Kubro Binjai, North Sumatra. This study used a descriptive-qualitative method. This research uses Hilda Taba's theory of curriculum development to explain the facts systematically. The results showed that the development of islamic boarding school-based madrasah curriculum at MAS Mizanul Kubro Binjai consisted of the following steps: 1) The diagnosis of needs included the following principles: a) the principle of balancing religious and general knowledge; b) moral education; c) discipline; d) responsibility; 2) formulation of objectives that are based on the vision and mission of the institution and adjust them to national, institutional, curricular, and instructional goals. 3) selection and organization of content, namely through the matching and collaboration of the curriculum of the ministry of religion (madrasah) and local content (Islamic boarding schools). 4) selection and organization of learning experiences, including: a) learning management; b) learning methods; and c) life skills development programs. 5) evaluation, which includes: a) daily tests and assignments, b) mid and final semester examinations conducted by madrasah, and c) national examination conducted by the government